Syndrome in question - Ana Cláudia Cavalcante Esposito; Tânia Munhoz; Juliana Polizel Ocanha; Hélio Amante Miot (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Dermatomyositis is a rare inflammatory disease, autoimmune, with proximal myopathy associated with characteristic dermatological manifestations. In adults, 20-50% of the cases are paraneoplastic manifestation, being mandatory the workup for malignancy Herein we report a case of a woman with classic dermatological presentation of dermatomyositis and newly diagnosed breast cancer. In general, the clinical presentation of paraneoplastic dermatomyositis is more exuberant and manifestations may precede, concur or succeed the diagnosis of neoplasia. The prognosis of cases associated with breast cancer is worse than the idiopathic form. Treatment is based mainly on the resolution of the underlying disease, beyond immunosuppressants.